Analisis Penerapan Metode On Page Off Page Pada Penentuan Berita Untuk Penaikan Trafic Di Website Vendoroutbound - Khoirul Annisa Febriana; Nur Khafidhoh (Kampus Akademik Publiser, 2025)
This study aims to improve the visibility and performance of the VendorOutbound.com website through the integrated application of on-page and off-page Search Engine Optimization (SEO) strategies. The research was conducted using a Research and Development approach over a three-month period from February to July 2025. The initial analysis showed low organic search performance, with only one click, 667 impressions, a click-through rate of 0.1%, and an average position of 42.5 on Google Search results. The optimization process involved improving the site structure, enhancing content with relevant keywords, optimizing images with descriptive file names and alternative text, refining meta tags, and building high-quality backlinks from relevant and authoritative websites. Post-implementation measurements using Google Search Console indicated significant improvements, including an increase in total clicks to 173, impressions to 27.8 thousand, and an improved average position of 16.3. These results demonstrate that a well-planned and consistently applied SEO strategy can significantly enhance search engine rankings, expand audience reach, and support the effectiveness of digital marketing efforts. Furthermore, the findings provide practical insights for service-based businesses, particularly in the outbound tourism sector, to optimize their online presence and increase organic traffic sustainably.